Characterization of Biofilm Formation by the Dermatophyte Nannizzia gypsea - Bruno B. A. Arantes; Ana Karla L. F. Cabral; Kelvin S. dos Santos; Matheus B. Mendonça; Rafaela C. dos Santos; Beatriz C. M. Bugalho; Lígia De S. Fernandes; Luis R. Martinez; Ana Marisa Fusco-Almeida; Maria José S. Mendes-Giannini (Journal of Fungi)
Dermatophytosis is a fungal infection that affects the skin, hair, and nails, impacting approximately 25% of the global population. Nannizzia gypsea is a geophilic fungus that can cause infections in humans and animals. Several studies have been conducted regarding its virulence, or ability to cause disease. This species may produce keratinolytic enzymes and form biofilms, which can increase resistance to treatment. Thus, this study focuses on investigating the biofilm formation of N. gypsea isolated from canine dermatophytosis using an ex vivo hair model, its biofilm extracellular matrix macromolecular contents, and the expression of genes involved in the colonization of keratinized surfaces. The biofilm was analyzed for metabolic activity using the XTT reduction assay, crystal violet staining to measure biofilm biomass, scanning electron microscopy (SEM), and the presence of polysaccharides, proteins, and extracellular DNA in the biofilm extracellular matrix. The virulence genes subtilisin 7, fungalysin (extracellular metalloproteinase), and efflux pump (Multidrug and Toxin Extrusion Protein 2) were evaluated by qPCR, comparing the planktonic and biofilm phenotypes. N. gypsea formed a robust biofilm, which matured after 5 days. Scanning electron microscopy (SEM) revealed the presence of an extensive extracellular matrix. In the hair model, the characteristic ectothrix parasitism of the species is observable. The gene expression analysis revealed a higher expression of all evaluated genes in the biofilm form compared to the planktonic form. Thus, N. gypsea exhibits a biofilm characterized by a robust extracellular matrix and high gene expression of factors related to pathogenesis and resistance.